An international review of markets for voluntary green electricity tariffs. (August 2018) - MacDonald, Scott; Eyre, Nick
Abstract: As many countries reduce or abolish centralised government support mechanisms for renewables, such as feed-in-tariffs, it is critical that researchers and policy makers examine other ways of supporting their development. Green electricity tariffs are one possible alternative, using the power of consumer demand to stimulate green electricity supply. This review is the largest ever study of markets for green electricity tariffs, covering 25 jurisdictions including many which have not been examined previously. The research finds that markets have grown significantly in recent years and, compared to the last comprehensive international study in 2002, the products are now available in many more countries. Those countries where green electricity tariffs have been on sale for longer periods of time have also seen significantly increased consumer uptake. A mixed methods approach is used to explore why some markets have seen more growth than others, as there is clear variation across the countries studied. High competition in energy markets is found to be a key driver of green tariff success, with the countries where consumers switched regularly more likely to have high enrolment. This factor has not been previously identified in the literature and highlights the importance of viewing green electricity tariffs in their wider regulatory context. Green tariffs are also found to be almost always more expensive than conventional electricity. While this may seem obvious, it highlights a weakness in some previous research which counterintuitively found that in many cases green electricity is cheaper than conventional electricity. The difference is explained by a change in methodology to one which recognizes that most consumers switching to green electricity are likely to be comparing against the cheapest conventional electricity supplier rather than simply the market average. Highlights: Established markets have seen considerable growth. Green tariffs are now available in many new markets. High competition in retail markets is a driver of green tariff success. Green tariffs are also almost always more expensive than conventional tariffs.